Linking linguistic intelligence and speaking anxiety in foreign language learning: a systematic review and integrative conceptual synthesis - Lanti Mustika Irtiani Irlan; Merry Lapasau; Widodo Widodo; Sumaryoto Sumaryoto (Lentera Negeri, 2026)
Speaking anxiety is a major affective barrier to oral performance in foreign language learning, while linguistic intelligence provides cognitive resources for vocabulary use, language organization, and verbal communication. Previous reviews have largely examined speaking anxiety separately, with limited attention to its interaction with linguistic intelligence across learning contexts. Guided by Gardner’s Multiple Intelligences framework and an affective perspective on foreign language anxiety, this study systematically synthesizes evidence on their relationship. Following PRISMA 2020, 35 studies published between 2020 and 2025 were selected from international databases. Eligible studies addressed foreign language learning and examined linguistic intelligence or competence, speaking anxiety, or related cognitive-affective factors. Methodological quality was appraised using the Mixed Methods Appraisal Tool (MMAT) Version 2018. Study selection and thematic coding were conducted by a single reviewer, and themes were developed through comparison and grouping of recurring findings. The synthesis indicates that stronger linguistic competence generally supports communicative readiness and lower speaking anxiety, although the relationship is context-dependent. Three broader conditions emerged: learner-affective factors, instructional-social conditions, and technology-supported practice. This review offers an integrative conceptual synthesis in which linguistic intelligence supports cognitive readiness for speaking, while affective and contextual conditions influence how effectively these resources are translated into speaking performance, rather than functioning as independent determinants of oral communication outcomes.